In Situ Measurement of Local Hydrogen Production Rate by Bubble-Evolved Recording - Xiaowei Hu; Liejin Guo; Yechun Wang (International Journal of Photoenergy)
Hydrogen visibly bubbles during photocatalytic water splitting under illumination with above-bandgap radiation, which provides a direct measurement of local gas-evolving reaction rate. In this paper, optical microscopy of superfield depth was used for recording the hydrogen bubble growth on Cd0.5Zn0.5S photocatalyst in reaction liquid and illuminated with purple light. By analyzing change of hydrogen bubble size as a function of time, we understood that hydrogen bubble growth experienced two periods, which were inertia effect dominated period and diffusion effect dominated period, respectively. The tendency of hydrogen bubble growth was similar to that of the gas bubble in boiling, while the difference in bubble diameter and growth time magnitude was great. Meanwhile, we obtained the local hydrogen production rate on photocatalyst active site by measuring hydrogen bubble growth variation characteristics. This method makes it possible to confirm local actual hydrogen evolution rate quantitatively during photocatalytic water splitting.